Free trade in the Americas : policy recommendations and isse papers (North-South Centre at the Univ. of Miami Coral GablesUS, 1997)
Presents private sector policy recommendations that were considered at the May 13-16 1997, Hemispheric Trade Ministerial and Americas Business Forum in Belo Horizonte, Brazil. Provides a report on the 1997 Hemispheric Policy Forum which focuses on the outlook for free trade in the Americas.
DC